2013
DOI: 10.1021/es304620x
|View full text |Cite
|
Sign up to set email alerts
|

Episode Analysis of Deposition of Radiocesium from the Fukushima Daiichi Nuclear Power Plant Accident

Abstract: Chemical transport models played key roles in understanding the atmospheric behaviors and deposition patterns of radioactive materials emitted from the Fukushima Daiichi nuclear power plant after the nuclear accident that accompanied the great Tohoku earthquake and tsunami on 11 March 2011. However, model results could not be sufficiently evaluated because of limited observational data. We assess the model performance to simulate the deposition patterns of radiocesium ((137)Cs) by making use of airborne monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 17 publications
5
89
0
Order By: Relevance
“…The model was designed to be easily handled and computationally efficient so that non-specialists of numerical simulations can conduct long-term assessments of atmospheric diffusion problems using their desktop or laptop computers. The LM was designed for rough budget estimates, as presented in the current study, or for sensitivity analyses using a large number of parameters (e.g., Groëll et al, 2014;Quérel et al, 2015;Girard et al, 2016), rather than for process-oriented analysis (e.g., Morino et al, 2013;Katata et al, 2015) or sensitivity analyses of the physical and chemical parameters of aerosols (Adachi et al, 2013). Details of each process and parameter are described in Appendix A.…”
Section: Lagrangian Model and Simulation Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was designed to be easily handled and computationally efficient so that non-specialists of numerical simulations can conduct long-term assessments of atmospheric diffusion problems using their desktop or laptop computers. The LM was designed for rough budget estimates, as presented in the current study, or for sensitivity analyses using a large number of parameters (e.g., Groëll et al, 2014;Quérel et al, 2015;Girard et al, 2016), rather than for process-oriented analysis (e.g., Morino et al, 2013;Katata et al, 2015) or sensitivity analyses of the physical and chemical parameters of aerosols (Adachi et al, 2013). Details of each process and parameter are described in Appendix A.…”
Section: Lagrangian Model and Simulation Settingsmentioning
confidence: 99%
“…Since then, a number of studies have been conducted, particularly during the months that followed the accident. These assessments include primary emission estimations (Chino et al, 2011;Danielache et al, 2012;Stohl et al, 2012;Terada et al, 2012;Katata et al, 2012aKatata et al, , b, 2015Winiarek et al, 2012Winiarek et al, , 2014Hirao et al, 2013;Saunier et al, 2013;Yumimoto et al, 2016;Danielache et al, 2016), field observations (ground aerosol sampling: Masson et al, 2011Masson et al, , 2013Kaneyasu et al, 2012;Adachi et al, 2013;Tsuruta et al, 2014;Igarashi et al, 2015;Oura et al, 2015;aircraft measurements: NRA, 2012; and measurements carried out on foot: Hososhima and Kaneyasu, 2015), and numerical simulations of transport and depositions (deterministic simulation: Chino et al, 2011;Morino et al, 2011;Yasunari et al, 2011;Stohl et al, 2012;Terada et al, 2012;Katata et al, 2012a, b;Winiarek et al, 2012Winiarek et al, , 2014Hirao et al, 2013;Saunier et al, 2013;Katata et al, 2015;Yumimoto et al, 2016;Danielache et al, 2016; deterministic simulation with sensitivity runs: Morino et al, 2013;Adachi et al, 2013;Groëll et al, 2014;Saito et al, 2015;…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the study of Korsakissok et al (2013) reported that the total deposition (sum of dry and wet deposition within a certain domain; in this paper, it is used interchangeably with ground deposition) from the Fukushima accident of 137 Cs (over land and within 80 km of FDNPP) is less than 1.5 × 10 15 Bq with the emission rate estimated by (Chino et al, 2011) but more than 5.5 × 10 15 Bq with the emission rate estimated by Stohl et al (2012). The importance of using accurate estimation of emission source strength has been also demonstrated by the sensitivity analyses of Morino et al (2013). However, previous studies solely focused on the emission rate, and other emission characteristics such as the gas partitioning of 131 I were also not considered.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 98%
“…Emission rate is another critical factor that controls the rate of atmospheric transport and ground deposition of radionuclides (Korsakissok et al, 2013;Morino et al, 2011Morino et al, , 2013. For instance, the study of Korsakissok et al (2013) reported that the total deposition (sum of dry and wet deposition within a certain domain; in this paper, it is used interchangeably with ground deposition) from the Fukushima accident of 137 Cs (over land and within 80 km of FDNPP) is less than 1.5 × 10 15 Bq with the emission rate estimated by (Chino et al, 2011) but more than 5.5 × 10 15 Bq with the emission rate estimated by Stohl et al (2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The ATDM used in these studies is WSPEEDI (Worldwide version of System for Prediction of Environmental Emergency Dose Information) [5] developed by the Japan Atomic Energy Agency (JAEA). Our source term has been validated by comparing with other estimations or by using in simulations of ATDMs [4,6,7]. The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) has used our source term [4] for estimating levels of radioactive material in the terrestrial environment and doses to the public, because they were derived from, and the models were already optimized to fit measurements of radioactive material in the environment [8].…”
Section: Introductionmentioning
confidence: 99%